2013
DOI: 10.1021/jp400440p
|View full text |Cite
|
Sign up to set email alerts
|

DFT+U Investigation of Propene Oxidation over Bismuth Molybdate: Active Sites, Reaction Intermediates, and the Role of Bismuth

Abstract: The mechanism by which propene is selectively oxidized to acrolein over bismuth molybdate has been investigated using the DFT+U variant of density functional theory. In agreement with experiment, the kinetically relevant step is found to be the initial abstraction of hydrogen by lattice oxygen. Several candidate lattice oxygen sites have been examined, the most active of which is found to be a bismuth-perturbed molybdenyl MoO oxygen. Hydrogen abstraction generates an allyl radical intermediate, which can diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
119
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(133 citation statements)
references
References 94 publications
14
119
0
Order By: Relevance
“…Jung et al [60] tested the influence of the pH value during co-precipitation of γ-Bi2MoO6 (initial ratio Bi/Mo = 2/1) on the oxidative dehydrogenation of n-butylene and discovered that the sample synthesized at pH = 3 showed both the highest butylene conversion and 1,3-butadiene yield due to a high oxygen mobility of this sample. According to the group of Keulks [8,20], re-oxidation of the catalyst is the rate-determining step in propylene oxidation at temperatures below 400 °C, whereas abstraction of an α-hydrogen atom to form an allylic intermediate is the rate determining step at higher temperatures (>400 °C), in agreement with theory [14]. Recently, it was further reported that the reaction order in oxygen was zero at 340 °C and 400 °C for Bi2Mo3O12 catalysts, i.e., the reaction rate for acrolein formation, was independent of the partial pressure of oxygen, indicating that the transition temperature where re-oxidation of the catalyst becomes the rate determining step was lower than 340 °C [61,62].…”
Section: Catalytic Performance In Propylene Oxidation To Acroleinsupporting
confidence: 70%
See 1 more Smart Citation
“…Jung et al [60] tested the influence of the pH value during co-precipitation of γ-Bi2MoO6 (initial ratio Bi/Mo = 2/1) on the oxidative dehydrogenation of n-butylene and discovered that the sample synthesized at pH = 3 showed both the highest butylene conversion and 1,3-butadiene yield due to a high oxygen mobility of this sample. According to the group of Keulks [8,20], re-oxidation of the catalyst is the rate-determining step in propylene oxidation at temperatures below 400 °C, whereas abstraction of an α-hydrogen atom to form an allylic intermediate is the rate determining step at higher temperatures (>400 °C), in agreement with theory [14]. Recently, it was further reported that the reaction order in oxygen was zero at 340 °C and 400 °C for Bi2Mo3O12 catalysts, i.e., the reaction rate for acrolein formation, was independent of the partial pressure of oxygen, indicating that the transition temperature where re-oxidation of the catalyst becomes the rate determining step was lower than 340 °C [61,62].…”
Section: Catalytic Performance In Propylene Oxidation To Acroleinsupporting
confidence: 70%
“…Nevertheless, the surface layer of these multicomponent catalysts consists of mixed oxides based on Bi and Mo, and these two metals seem to form the key active sites [13]. The rate-determining step is the abstraction of hydrogen from propylene on bismuth or bismuth connected to molybdyl groups [14]. The addition of other transition metals and main group metals helps to increase the specific surface area of the catalyst [15], the extent of lattice oxygen participation [15,16] and the electronic conductivity [17].…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is supported by DFT studies, which reveal further that the most reactive O atoms are those in Mo O bonds that interact with the lone pair of proximal Bi atoms (e.g. equatorial Mo O bonds) [15,16]. This interaction destabilizes the HOMO and stabilizes the LUMO of the molybdate species, thereby facilitating the transfer of an electron into a Mo O p* orbital.…”
Section: Catalystmentioning
confidence: 74%
“…The principle catalysts used to promote this reaction are bismuth molybdates in which a part of the molybdenum is substituted by one or more other metals in order to enhance the catalyst activity and selectivity [3][4][5][6][7][8][9][10]. A number of groups have investigated the mechanism of propene oxidation on ␣-Bi 2 Mo 3 O 12 with the aim of understanding the elementary processes leading to acrolein and the influence of added elements on these processes [11][12][13][14][15][16]. These efforts have led to the following findings.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and computational results have indicated that the critical alkene activation step occurs at the methyl group of propene by a Bi-O function in the bismuth-molybdate catalysts [4][5][6][7][8][9]. Supported catalysts incorporating bismuth have also been shown to catalyze the oxidation of different aromatic and alkane compounds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%